ANALISIS PENGAMBILAN KEPUTUSAN DALAM KENDALA DI UMKM BAKMI JOWO PAK YOS - Aziz, Aditya Lukman; Aura Nuraini; Gaida Listia Nurayuni; Kaka Rapi Kurnia; Ujang Suherman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy; however, they continue to face various challenges that affect business sustainability. This study aims to analyze the decision-making process in addressing business constraints at Bakmi Jowo Pak Yos MSME in Karawang Regency using a qualitative descriptive approach through observation, interviews, and documentation, with the business owner as the main informant. The results indicate that decision-making is influenced by constraints related to labor management, capital, raw materials, and marketing, with decisions being practical, adaptive, and experience-based, focusing on business continuity. Although decisions are not made through formal and structured procedures, they have proven effective in maintaining operational stability amid limited resources and dynamic business conditions.